Inculcating Values and Ethics in Higher Education e-Learning Drive: UiTM i-Learn User Policy - Mohd Isa, Posiah; Abu Samah, Siti Akmar; Jusoff, Kamaruzaman (2008)
With the advent of cyber technology, one aspect of teaching is starting to take root in the institution of higher education and that is e-learning. The current scenario in the education sector of developing countries such as Malaysia is also experiencing the beginning of participation in the exploration and exploitation of e-learning initiatives. Like in many other trends, be it social, economic or political, put forth, particularly from the propagation of ideas of the western countries, developing countries take on to these like wild bush fire. This is also observed in the education sector. This paper attempts to address some of the challenges that have cropped up as far as learning with technology is concerned. The borderless realm of knowledge warrants behaviour that may lead to academic dishonesty. In frequent observations, some actions on the part of the students may precariously endanger the credibility of their assignments, projects and evaluation. To sustain these values for the good of their future, we need to address these challenges and to make known to these students the implications that these behaviour create on their study and their future. Some considerations have been discussed in the subsequent part of the paper to help curb academic dishonesty in the university. The role taken by the institutions of higher education has to be comprehensive, if not total. It is particularly important that the management of student affairs, the faculty and several other parties be able to see these issues as very serious before the undesirable elements of technology usage sits deeply enrooted in the teachinglearning process. After all, the future of a nation depends on the stewardship of these students when they graduate one day and work in the government or private sectors of the country.